Podcast “pod... O quê? Cast” jornalismo especializado no mundo dos podcasts - Souza, Ariany Minister de (Universidade Federal do Tocantins, 2022)
This work presents the Podcast POD... O QUÊ? CAST, a journalistic product, in the style of a specialized electronic magazine, which aims to offer tips, reviews, analyzes and interviews about the universe of podcasts, also producing a service for a niche consumer audience and podcast producer, although it may, also, to be a program that instigates new followers of this type of media. The research on which this proposal was based, of an exploratory and bibliographic nature, raised theoretical data on the subject and identified the presence/types of podcasts on the internet. From the data, which anchored the discussion present in the memorial about this sound media and related to the proposed product, the steps to produce the episodes that make up the prototype of the podcast were defined. We set out to produce 3 (three) episodes, seeking to embrace opinions from professionals in the field to present the perspective of podcast producers. We also chose to have an academic look at the theoretical aspects of the topic. The selection of respondents was based on their academic background and experience with this media tool. Through the research, it was possible to understand the distinction between radio and podcast, which elements are considered by podcasters when designing their shows, as well as experiencing the production experience. It is concluded that the project demonstrates the possibility of alternative journalistic work, which can create a space for dialogue about the universe of podcasts, their uses and information possibilities.